Religiosity and tax: A systematic review - Wicaksono, Galih; Widarjo, Wahyu (Jurnal Akuntansi dan Auditing Indonesia, 2025)
This study aimed to analyze the growth of research topics germane to religiosity and taxes globally, as an initiative to capture current and future research trends. Religiosity and taxes have received extensive research emphasis at the global level, due to the mounting role of religiosity in driving tax behavior. This research began with an analysis using VOSviewer to locate publications from 2005 to 2024, allowing a systematic review of related works involving such keywords as religiosity and taxes published over the past ten years. Globally, studies on religiosity and taxes have increased in the past five years, especially in European, Asian, and American countries. Our analysis reveals four topical clusters encompassing religiosity and taxes. The analysis also unfolds four theories related to religiosity and taxes: the theory of planned behavior, social influence theory, economic deterrence theory, and religious commitment theory. The novelty of this study lies in the discussion on the relationship between religiosity and taxes, so that current and future research trends can be identified. The research limitation is that it is only sourced from the Scopus database.